Zirconia/dental pulp stem cell composite scaffolds repair osteogenic defect via regulating macrophages - Wu, Yingying; He, Maodian; Li, Cuimei; Shang, Weihua; Hu, Jiale; Liu, Bingyao (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundDental pulp stem cells (DPSCs) possess multilineage differentiation potential and immunomodulatory properties, making them promising candidates for bone regeneration. In this study, the regenerative potential of DPSCs combined with nitrogen-doped reduced graphene oxide/zirconia (N-Rgo/ZrO2) composite scaffolds was investigated in vitro and in a rat jaw injury model.MethodsThe primary human DPSCs were characterized by flow cytometry (CD90/CD29/CD45) and trilineage differentiation assays. In vitro effects on macrophage polarization (IL-6, TNF-α, CD206, Arg1, iNOS, IL-10) and MAPK signaling (p-ERK1/2, p-p38) were analyzed using qRT-PCR and Western blot. A rat bone defect model was established to evaluate mandibular bone regeneration through H&E staining, Masson’s trichrome, and molecular analysis of osteogenic markers (RUNX2, ALP, Osterix, OPN, OCN) and pathway activation.ResultsDPSCs exhibited characteristic mesenchymal markers (CD90+: 90.16% ± 1.00%; CD29+: 99.27% ± 0.11%) and multilineage differentiation capacity. N-Rgo/ZrO2+DPSCs synergistically upregulated M2 macrophage markers (CD206, Arg1, IL-10) and pro-osteogenic cytokines (TNF-α) while suppressing IL-6. This combination potently activated p-ERK1/2 and p-p38 MAPK, exceeding single-treatment effects. In vivo, cotreatment restored trabecular architecture (collagen fiber density), improved rat pathological conditions, and significantly elevated osteogenic markers (RUNX2, ALP, Osterix, OPN and OCN) compared with monotherapies.ConclusionThe N-Rgo/ZrO2+DPSCs composite promotes bone regeneration through dual mechanisms: (1) immunomodulation through M2 macrophage polarization and MAPK pathway activation and (2) direct osteogenic differentiation. This strategy demonstrates superior efficacy to individual components, offering a novel combinatorial approach for maxillofacial bone repair.